COVID-19 — Important considerations for developing and using a vaccine - Rahman, Inayat Ur (Hum Vaccin Immunother, 2020)
The novel coronavirus SARS-CoV-2 after emerging in China has caused a global pandemic that is risking the lives of millions. COVID-19 has spread across the world at a very rapid rate raising concerns of capacity limitations and lack of unified responses at the global level, particularly from the world’s most developed countries. The spread of further infection has been curtailed by lockdown and mass social distancing that has been enforced in most parts of the world. There are no clinical data yet suggesting that any available candidate vaccine will be effective for COVID-19 which will be a critical need for eventually preventing this disease. Extensive research is underway with some success in identification of monoclonal antibodies from COVID-19 recovered patients, which may inform on vaccine development. The clinical evaluations of COVID-19 vaccines need to follow standardized protocols that are essential for safeguarding humans. In absence of a vaccine or a widely available effective therapy, quarantine and other preventive measures are essential in curtailing the risk of pandemic spread.